The evaluation of an embedded system kit as a c programming teaching tool - Suliman A.; Nazeri S. (Universiti Utara Malaysia Press, 2023)
This paper describes the methodology used in evaluating the effectiveness of an embedded system teaching tool for C programming. Teaching programming is one of the major problems among schools and universities. To overcome this problem, a teaching module and an embedded-system training kit for teaching programming to beginners were developed. The teaching module and kit were then tested on selected groups of school children. Focusing more on the testing phase of the research work, this paper gives a detailed account of the testing process and the evaluation method used. The result shows that the students are interested to learn programming using the embedded system.